Intellect, Eikona and 'Beholding' in Gregory of Nyssa's On the Human Image of God. - Laird, Martin (International Journal of Systematic Theology, 2026)
In John Behr's edition of Gregory of Nyssa's On the Human Image of God, he identifies Chapter 16 of the treatise as a pivotal connecting chapter connecting the first and second parts of the book – taking up again, as it were, the exposition of human creatures as made 'in accordance with' the divine image and likeness. In his response, Martin Laird argues that Chapter 16.9 consummates the organic development of the human as the 'apex of creation and ... the very image of God'. Moreover, Laird sees a connection between Chapter 15.3 and Chapter 16.9. Set off by several of Gregory's apophatic markers, Chapter 15.3 presents the apophatic nature of the intellect which constitutes the key to understanding the key phrase in Chapter 16.9 that declares that 'there is to be beheld in the human compound a share ... of the divine'.